PERANCANGAN CLOUDSTORAGE KEGIATAN KEHUMASAN PADA BIRO HUMAS, PROMOSI DAN PROTOKOL PADA BP BATAM - Afrina Afrina; Novi Hendri Adi (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The role of PR has a big role in recording the development and journey of the Batam Concession Agency (BP) from time to time. The importance of documentation activities defines documentation as the activity or process of providing documents using accurate evidence based on recording various sources of information. So that users do not have to look for storage media from year to year by coming directly to the office, but simply by accessing the Batam Concession Agency (BP) public relations activity documentation website easily and does not take a long time. The design method used in designing this documentation will use the MDLC (Multimedia Development Life Cycle) design method with the stages of planning, analysis, design, implementation and UML modeling